Analisis Marketing Mix dalam Meningkatkan Jumlah Pembeli Ayam Geprek Mbok Moro Kota Kediri - Forijati, Forijati; Ridwan, Ridwan (Efektor, 2020)
The purpose of this research is to find out how the marketing mix is ​​used to increase the number of buyers in the Mbok Moro Geprek Chicken Business. Marketing activity is an attempt to offer consumers the products they are produced. Marketing is a very determining factor for the survival of a company, so it is very important for business owners to pay attention to the marketing mix that the company runs. The research method used mixed method. The subject of this research was Mbok Moro geprek chicken business and ata collection used interviews and observations. Data analysis techniques used marketing mix analysis. The variables of marketing mix were product, price, place and promotion. The result of this research showed that consumers’ decision to buy Mbok Moro Geprek Chicken had many reasons, they are: the place was strategic and the price of product was afforadable. The recommendation of this research is that the products of Mbok Moro geprek chickens must be more varied and innovative in packaging and online marketing and also improving brand.